Continuous simulations of nutrients and BOD through a stream section - Imteaz, M.; Hossain, I.; Anwar, Faisal (2015)
This paper presents development of a one-dimensional stream water quality model for the continuous simulations of suspended sediments, biochemical oxygen demand (BOD), total phosphorus (TP) and total nitrogen (TN) along a particular stream section. The model first integrates stream hydraulics and suspended sediments transport and deposition processes. Then computations of degradation of water quality parameters (BOD, TP and TN) are incorporated with the hydraulic-sediment transport model. The stream hydraulic model was developed using Muskingum-Cunge method of channel routing. The well known suspended sediment transport/deposition processes have been modified and integrated with the developed hydraulic model. The developed water quality model was applied and simulated for the Saltwater Creek, Gold Coast, Australia. Sensitivity analysis of the model showed that all the particles characteristics within incoming stream flows are important for the better prediction of suspended sediment loads.